LONG-TERM ACTIVITY CHANGES OF UV PISOIUM - Keskin, V.; Tunca, Z.; Ibanoglu, C.; Aslan, Z.; Selam, S. O.; Muyesseroglu, Z. (Одеські астрономічні публікації, 2017)
UV Psc has been observed since 1976 at the Ankara and Ege University Observatories. Mean light curves in B and V colours obtained using the maxima levels of observed light curves of the system. Assuming this light curves as the least active onesj the orbital parameters of the system have been obtained using the Wilson- Devinney code. The radial velocity curves of both components have been used during the solution. Wave-like distortion curves for each year have been obtained subtracting the theoretical light curves from the observed ones. Using these curves, the spot parameters have been roughly determined and finally spotted light curve solutions and the accurate spot parameters have been obtained. Activity and colour behaviour were examined.